A BRIEF SKEPTICISM: THE DISCOURSE OF THE COPENHAGEN SCHOOL AND CYBER SECURITY IN INDONESIA - Ghiffary Abdurrahman, Muhammad Kamil; Marulitua Gultom, Yosua Saut (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
The evidence shown from the last decade shows that Indonesia has been the constant target of cyber attacks, hence, the urgency to respond cyber threats with its according and appropriate response: a more securitized response. The existing literatures, however, have shown that the academic discourse national retaliation against the cyber threat is rarely guided by the Copenhagen School’s Securitization Theory, which has established a massive gap on why the the discourse has not been the mainstream approach on tackling Indonesia’s national threat on its cyber infrastructures. As a conclusion, the analytical lenses by the Barry Buzan and Ole Waever is strictly adopting concepts to define its own securitization process, but each concepts are still lacking of the depth required to wholefully understand how ideal securitization should and would work. Nonetheless, putting a state’s political actor as the securitization actor deemed to be putting too much emphasize as the state as the main national stakeholders, putting the society in an absurd position within the process of securitization.